KAUSALITAS KONTRIBUSI INDUSTRI PARIWISATA DAN JUMLAH KUNJUNGAN WISATAWAN TERHADAP PERTUMBUHAN EKONOMI - YUDISTIRA, COKORDA BAGUS; SUMARJAYA, I WAYAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 7 No 4 (2018)DO - 10.24843/MTK.2018.v07.i04.p222, 2018)
Bali is known as one of the most popular tourism destination in the world. The number of tourist visit to Bali increases every year. In 2010, there roughly 7 millions tourist visits to Bali and reach up to 14 million people by the end of 2017. This increased in number may affect the growth of tourism industries and economic growth in Bali Province. This study aims to analyze the patterns of causal relationship between tourism industry receipts, tourist visits, and economic growth in Bali based on time series data using vector autoregressive (VAR) model. The results conclude the following: (i) foreign tourist visits is significantly affect economic growth. In addition, economic growth, domestic tourist visits, and foreign tourist visits are significantly impact to tourism industry receipts, (ii) economic growth would affect the tourism industry receipts in the next four consecutive months, (iii) the forecasting result of economic growth with VAR model is highly accurated with MAPE 2%.